A case study of waste auditing in an oleochemical plant - Fauziah, S.H.; Agamuthu, P. (Malaysian Journal of Science, 2001)
This paper describes the results of a waste audit conducted in a leading manufacturer of basic oleochemical products in Malaysia. The two principal wastes generated by the facility are wastewater sludge and glycerol residue, with a daily production of 3.0 tonnes and 1.0 tonne, respectively. Besides glycerol residue, which is classified as scheduled waste, the process operations also generated 1.17 tonnes/day of other hazardous wastes including spent chemicals and contaminated items. Currently, 65% of the total solid waste generated by the plant is recycled and reutilized within the premises. The administrative center alone contributed as much as 21.17 kg/day of waste paper and 1.71 kg/day of plastic waste. Results from the waste audit indicated that the percentage of recycling could be increased with the implementation of cleaner technology to almost 75% ofthe total waste generated by reutilizing more identified items within the facilities. Besides the reduction in waste generation, the cost of purchasing the reutilized items would also decrease, as well as the cost of waste disposal.